Study of Empowerment of women and its various parameters - Gitesh Kalita (Innovative Research Thoughts, 2023)
Empowering women is an essential component in developing a society that is equitable and just. It is an idea that tries to guarantee that women have equal access to opportunities, resources, and rights; that they are able to exercise their agency; and that they are able to make choices about their life that are based on accurate and up-to-date information. The process of empowering women is intricate and multi-faceted, taking into account a wide range of social, economic, political, and cultural variables. It needs the removal of patriarchal norms and behaviour that, among other things, restrict the possibilities available to women and propagate discrimination on the basis of gender. The empowerment of women results in substantial advantages for the whole of society. Empowering women may lead to higher economic development, better health outcomes, and more effective government. Women are a tremendous resource that is underused in many communities. Empowering women can lead to increased economic growth. Women who have more agency in their lives are also more inclined to invest in their families and communities, which may have a beneficial impact, both socially and economically, on future generations.